MENGUNJUNGI “MUSEUM” SENI PURBA DI KALIMANTAN - Bambang Sugiyanto (Balai Arkeologi Kalimantan Selatan, 2010)
Kalimantan is wellknown for its karst environment, which bear rock shelters and caves. Apparently, the karst environment in East Kalimantan provides important information on prehistoric human occupation, especially human’s appreciation toward narure in the form of art. The art in Marang is illustrated on cave walls as rock paintings of hand imprints and other images. Such presentation may be comparable to a museum display, however, it present in situ data with more invaluable cultural and historical information. This article discusses the uniquensess of materializing human’s sense of art on cave wall and their role as ‘museum’ for the benefit of future generation.